Violent behavior and the network properties of psychopathological symptoms and real-life functioning in patients with schizophrenia - Chen, Li-Chang; Tan, Wen-Yan; Xi, Jun-Yan; Xie, Xin-Hui; Lin, Hai-Cheng; Wang, Shi-Bin; Wu, Gong-Hua; Liu, Yu; Gu, Jing; Jia, Fu-Jun; Du, Zhi-Cheng; Hao, Yuan-Tao (Frontiers in Psychiatry, 2024)
Objective To assess the interplay among psychopathological symptoms and real-life functioning, and to further detect their influence with violent behavior in patient with schizophrenia. Methods A sample of 1,664 patients with post-violence assessments and their propensity score–matched controls without violence from a disease registration report system of community mental health service in Guangdong, China, were studied by network analysis. Ising-Model was used to estimate networks of psychopathological symptoms and real-life functioning. Then, we tested whether network properties indicated the patterns of interaction were different between cases and controls, and calculated centrality indices of each node to identify the central nodes. Sensitivity analysis was conducted to examine the difference of interaction patterns between pre-violence and post-violence assessments in violence cases. Results Some nodes in the same domain were highly positive interrelations, while psychopathological symptoms were negatively related to real-life functioning in all networks. Many symptom-symptom connections and symptom-functioning connections were disconnected after the violence. The network density decreased from 23.53% to 12.42% without statistical significance (p = 0.338). The network structure, the global network strength, and the global clustering coefficient decreased significantly after the violence (p < 0.001, p = 0.019, and p = 0.045, respectively). Real-life functioning had a higher node strength. The strength of sleeping, lack of spontaneity and flow of conversation, and preoccupation were decreased in post-violence network of patients. Conclusion The decreasing connectivity may indicate an increased risk of violence and early warning for detecting violence. Interventions and improving health state based on nodes with high strength might prevent violence in schizophrenia patients.